Role of information sources in carrying government reproductive health scheme to tribal women in India: A case study among women belonging to Koraga community - Nandini Lakshmikantha; Shivalingappa B. Javali (Journal of Family Medicine and Primary Care)
Context: To improve the health status of its people irrespective of their socio and economic status, the government will design various schemes. In taking the government schemes effectively to the target group, the role of information sources is crucial. For the study purpose, Koraga community residing in and around Udupi—a district of Karnataka State, which has earned a name not only for its mythological significance but also for its culture of having their women empowered is considered. In the present study, role of information sources in taking the Janani Shishu Kalyan Yojana planned towards improving the pre- and post-natal health of women to reduce maternal death is considered. The results of the study enable us to understand the preference and dependency of the target group on various sources regarding the information received. Since the government-proposed health schemes should reach the target group to bring in a better health index which is one of the SDGs set for 2030, this study gains importance. Aims: The study intends to examine the role of information sources in educating the women, particularly those belonging to Koraga community, who fall under the particularly vulnerable tribal groups (PVTG) category among the tribals of India about the government schemes earmarked for safe motherhood. Settings and Design: It was conducted in the colonies designated for Koraga community near Udupi of Karnataka using a questionnaire. Materials and Methods: Based on the results obtained from the pilot study, a final questionnaire was prepared and was personally demonstrated among Koraga women during the month of January 2020. Data were collected from 117 women belonging to Koraga community. SPSS version 17.0 software, Microsoft Word and Excel were used in data handling and analysis. Results: The results obtained out of the study reveal that among the sources, the respondents consider doctors as dependable sources followed by ASHA/Anganwadi workers. The target group is not aware of the nomenclature of the scheme nor the benefits to expect, but they are receiving medical support during their pre- and post-natal period. Conclusion: The governments may initiate schemes for the benefit of the public, but the schemes will become successful only when the desired information reaches the target group. The study intended to examine the role of information sources in educating the women particularly those belonging to Koraga community and found that the dependency of the target group on various sources of information regarding government projects is evident and should be further strengthened.